Balancing convenience, affordability, and nutrition: an evaluation of ready-to-eat meal preferences among UiTM students and the effectiveness of the Menu Rahmah initiative - Lee, Noor Azli Affendy; Rozli@Rosli, Mohd Ikmal Fazlan; Abd Ghani, Kay Dora; Sulaiman, Suria; Zaini, Intan Rabiatulainie (Universiti Teknologi MARA, Kedah, 2025)
This study explores the consumption habits and preferences for ready-to-eat (RTE) meals among students at a northern Universiti Teknologi MARA (UiTM) campus, with a focus on evaluating the effectiveness of the Menu Rahmah initiative, which offers affordable meal options on campus. A survey of 318 students revealed a high level of familiarity with RTE meals, with nearly half of the respondents consuming these meals daily or several times a week. The primary factors influencing their choices include convenience, time-saving benefits, and price. However, the study also highlights significant concerns regarding the affordability and nutritional quality of RTE meals. Many students expressed a desire for healthier, more nutritious options and indicated a willingness to pay more for better quality meals. The Menu Rahmah initiative was generally well-received, though students suggested improvements in portion size, variety, and food quality. The findings underscore the need for universities to expand and improve RTE meal offerings to better meet the dietary needs and preferences of their students, balancing convenience, affordability, and nutritional value.